Preparation method of aluminum alloy plate with high formability, high strength and high corrosion resistance
By increasing the Cu content and using Fe elements to form a multi-scale gradient distribution Al FeCu phase, and performing multi-process thermal processing and regulation, the forming performance and corrosion resistance of Al-Zn-Mg-Cu-based aluminum alloy on the body structural parts is solved. The problem of insufficient, high strength and corrosion resistance aluminum alloy sheets are achieved, which are suitable for the manufacturing of automotive body structural parts.
Patent Information
- Application Number
- CN202411344312.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
The stamping forming performance, strength and corrosion resistance of Al-Zn-Mg-Cu-based aluminum alloy on the body structural parts is insufficient, resulting in high cost, poor forming performance and corrosion resistance in automotive lightweight applications. .
By increasing the Cu content and using the Fe elements in the aluminum, a multi-scale gradient distribution Al FeCu phase is formed, and multi-process hot processing is carried out, including dual-stage high-temperature heat treatment, hot rolling deformation and non-isothermal pre-aging treatment, optimizing the alloy's The grains and precipitation phases are distributed to improve their forming performance and corrosion resistance.
The room temperature stamping and corrosion resistance of Al-Zn-Mg-Cu-based aluminum alloy sheets are significantly improved, ensuring that high strength remains after simulated paint baking, reducing production costs, and suitable for the manufacturing of complex shape parts.
Smart Images

Figure CN119287231A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloys, and is particularly aimed at the fact that the forming performance, strength and corrosion resistance of aluminum alloy sheets for vehicle body structural parts are still not high enough, and the application status of the automotive field with continuously increasing requirements for these performances, and proposes a processing method for improving the forming performance, strength and corrosion resistance of Al-Zn-Mg-Cu alloys that can be industrially applied. The processing method can effectively control the distribution of grains and precipitated phases in the alloy, and form organizational characteristics that have a significant promoting effect on the forming performance, strength and corrosion resistance of the alloy. Background Art
[0002] With the continuous improvement of the level of industrialization, the energy crisis and environmental problems have become more and more serious, and energy conservation and emission reduction have become the main theme of future development. Against this background, countries have adopted many measures to solve energy consumption and environmental problems, especially in the automotive field: how to improve the efficiency of automobile engines, develop new energy vehicles, and reduce the weight of automobiles have become recent research hotspots, and major automobile manufacturers are constantly developing lightweight solutions that can enhance their competitiveness. Overall, aluminum alloys have become the key materials for lightweight automobiles due to their light weight, corrosion resistance, high specific strength, easy processing, beautiful surface, abundant reserves, and recyclable recycling. In addition, according to statistics, the energy saved by using aluminum alloys in automobiles is 6 to 12 times the energy consumed by the original aluminum used to produce the parts. Therefore, the development and application of advanced aluminum alloy sheets for lightweight automobiles has attracted widespread attention from automobile manufacturers and scientific researchers around the world, which has led to an increase in the amount of aluminum used in automobiles year by year in recent years.
[0003] Compared with other series of aluminum alloys, Al-Zn-Mg-Cu (7xxx series) aluminum alloys have been widely used in the aerospace field due to their excellent high strength and toughness. However, with the acceleration of the lightweight process of automobiles, especially with the continuous application of 5xxx and 6xxx series aluminum alloys, it is urgent to use the high-strength 7xxx series aluminum alloys widely used in the aerospace field for the manufacture of body structural parts, so as to effectively solve the problems of difficult connection between the aluminum alloy of the body outer panel and the steel structural parts and poor corrosion of heterogeneous metals. However, high-strength 7xxx series aluminum alloy sheets generally have problems such as high cost, poor stamping forming performance, and corrosion resistance that needs to be further improved. These problems have become the key issues restricting the widespread application of this series of aluminum alloys in body structural parts. Recently, a large number of studies have shown that hot forming or warm forming can promote the forming performance of this series of aluminum alloy sheets, but the forming process is complicated and the production cost is high. In addition, it is easy to affect the distribution of the precipitated phase during warm and hot forming, thereby reducing the strength of the alloy sheet, which is very unfavorable for the widespread application of this series of alloys in body structural parts. It can be seen that in order to better meet the needs of actual applications, it is urgently necessary to improve the room temperature stamping forming performance of this series of alloy sheets through composition design and process control, and through subsequent process control, it can be made to have both high strength and high corrosion resistance. This is of great significance for rapidly advancing the lightweight process of automobiles and the widespread application of high-strength 7xxx series aluminum alloy materials in body structural parts. Summary of the invention
[0004] In order to better meet the urgent demand for high-performance aluminum alloy plates for lightweight automobiles, the present invention proposes a composition design and corresponding preparation method of Al-Zn-Mg-Cu alloy plates with high formability, high strength and high corrosion resistance in view of the problems of poor matching of stamping forming performance, strength and corrosion resistance of traditional Al-Zn-Mg-Cu alloy plates. The present invention makes full use of the high content of solute element Fe generally contained in recycled aluminum or ordinary aluminum. By increasing the Cu content, it can not only be dissolved in the alloy matrix, but also form a concentration gradient distribution feature with Fe element in the cast state, and further form Al-FeCu phases with multi-scale gradient distribution through subsequent hot rolling and high-temperature heat treatment; at the same time, with the change of hot working process, the size matching, morphology and distribution of these phases can change significantly, which has an important impact on the alloy organization and texture evolution. In particular, the multi-scale iron-rich phase with gradient distribution characteristics in the alloy matrix during the subsequent high-temperature solution heat treatment will have a positive effect on the alloy recrystallization nucleation, that is, coarse particles can induce recrystallization nucleation, while fine particles can effectively hinder the rapid growth of recrystallization, which will eventually effectively refine the grains and significantly weaken the texture, and the stamping performance of the pre-aged alloy sheet can be significantly improved. In addition, due to the increase in the solute element Cu content, a large number of solute atomic clusters can be further precipitated on the original basis through double-stage pre-aging regulation, which can improve the coordinated deformation ability between grains in the alloy matrix and further improve the stamping performance of the alloy sheet. For pre-aged alloy plates, if they are subjected to variable-rate non-isothermal heat treatment, not only can the precipitation of continuous precipitate phases at grain boundaries be effectively inhibited, thereby greatly improving the corrosion resistance of the alloy, but a large number of multi-scale precipitate phases can also be precipitated in the alloy matrix, so that the alloy plates can still exhibit high-strength characteristics after simulated baking paint (170-185℃ / 20-30min), while the strength will be reduced after the traditional isothermal aging process is regulated and then subjected to simulated baking paint treatment.
[0005] According to a first aspect of the present invention, there is provided a method for preparing an Al-Zn-Mg-Cu aluminum alloy sheet having high formability, high strength and high corrosion resistance, wherein the aluminum alloy is an Al-Zn-Mg-Cu-Fe-Mn alloy, and the chemical composition and its mass percentage content are: Zn: 5.0-7.0wt%, Mg: 1.0-3.0wt%, Cu: 1.5-4.0wt%, Fe: 0.1-0.6wt%, Mn: 0.05-0.2wt%, Ni: 0.02-0.05wt%, Ti: 0.02-0.2wt%, Cr: 0.01-0.03wt%, Si: 0.01-0.07wt%, and the balance is Al;
[0006] It is characterized by adopting the following technical route:
[0007] (1) Using recycled aluminum or ordinary aluminum to prepare Al-Zn-Mg-Cu-Fe-Mn alloys with high formability, high strength and high corrosion resistance, then using medium frequency induction melting under non-vacuum conditions, and casting them in a water-cooled steel mold, the cooling rate is controlled to be greater than 40°C / min so that the alloy grain size, solute element segregation and primary phase distribution meet the subsequent regulation requirements;
[0008] (2) According to the as-cast structure, the ingot is subjected to a two-stage high-temperature heat treatment, wherein the first stage temperature is 390-430°C, the heating rate is 22-35°C / min, and the treatment time is 10-27h; the second stage temperature is 430-485°C, the heating rate is 22-35°C / min, and the treatment time is 10-27h; then the ingot subjected to the high-temperature heat treatment is further cooled to 410-438°C, the cooling rate is 5-15°C / min, and then hot rolling deformation treatment is performed on it, and the hot rolling deformation amount is 40-68%;
[0009] (3) Then, the hot-rolled plate is subjected to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-510° C., and the treatment time is 0-30 h;
[0010] (4) Subsequently, the alloy plate subjected to the primary heat treatment is subjected to a secondary hot rolling deformation treatment, the alloy plate is directly placed in a 410-428° C. heat treatment furnace for 10-60 min, and then subjected to hot rolling deformation, with a hot rolling deformation amount of 50-80%;
[0011] (5) The hot-rolled plate is then subjected to secondary high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, with the heat treatment temperature being 460-510° C. and the treatment time being 0-30 h;
[0012] (6) then sequentially performing a certain amount of primary cold rolling deformation + intermediate annealing treatment + secondary cold rolling treatment, so that the alloy matrix precipitation phase and the iron-rich phase present a coupled gradient distribution characteristic;
[0013] (7) High temperature short time solution treatment, solution temperature 470-500℃, then quenching and cooling the alloy sample from the solution treatment temperature to room temperature, transferring the quenched sample to the aging furnace within 1 min for double-stage isothermal pre-aging treatment, the first stage temperature is 80-140℃, the second stage temperature is 20-60℃, the alloy sheet can show excellent room temperature stamping performance;
[0014] (8) The samples treated with double-stage pre-aging were then subjected to non-isothermal heat treatment, and the variable-rate variable-temperature aging process was set to three stages, namely, 100°C → 170°C (heating rate R H1 )→185℃(heating rate R H2 )→170℃(cooling rate R C1 )→100℃(cooling rate RC2 ), where R H1 =R C2 =10-30℃ / h, R H2 =R C1 =30-50℃ / h, raise the sample temperature to 185℃, or further cool it to 170℃; the alloy can show high strength and high corrosion resistance.
[0015] Based on the above-mentioned multi-process control of the iron-rich phase, grain size, morphology and orientation distribution, and coupled distribution of intracrystalline and grain boundary precipitation phases, it can be ensured that the developed alloy sheet has excellent stamping forming performance, high strength and high corrosion resistance.
[0016] Furthermore, in step (1), the alloy melting process using medium frequency induction under non-vacuum conditions is as follows: first, all the recycled aluminum or ordinary aluminum is added to a crucible and melted, the temperature is controlled at 780-880°C, and then Al-20wt% Fe, Al-10wt% Mn, Al-10wt% Ti, Al-5wt% Cr, Al-20wt% Si master alloys are added respectively, and after melting, Al-50wt% Cu master alloy is added, and then the melt is stirred at high power for 9-11 minutes, and then the required content of pure N is added. i into the melt and stir the melt with high power for 9-11 minutes, then control the temperature of the alloy melt to above 720°C, add pure Zn and pure Mg respectively, press it into the bottom of the melt with a graphite bell when adding pure Mg, take out the bell after it is completely dissolved, adjust the power of the medium frequency induction furnace to stabilize the temperature of the alloy melt at 740°C again, then skim the slag, add a refining agent for degassing and refining; then add Al-5wt% Ti-1wt% B grain refiner when the melt temperature is reduced to 720°C and stir appropriately, finally, after keeping the temperature at 720°C for 10 minutes, cast the melt into a steel mold with water cooling on all sides, and control the cooling rate to be greater than 40°C / min.
[0017] Furthermore, in step (2), the ingot is subjected to a two-stage high-temperature heat treatment, wherein the first stage temperature is 390-415°C, the heating rate is 22-32°C / min, the treatment time is 10-27h, and the second stage temperature is 430-485°C, the heating rate is 22-32°C / min, and the treatment time is 10-27h; then the ingot subjected to the high-temperature heat treatment is further cooled to 410-428°C, the cooling rate is 10-15°C / min, and then it is subjected to hot rolling deformation treatment, the hot rolling deformation amount is 40-68%, the pass deformation amount is 10-20%, and unidirectional rolling is performed.
[0018] Furthermore, in step (3), the hot-rolled plate is subjected to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-500°C, the treatment time is 0-30h, the heating rate is 22-32°C / min, and the cooling rate is greater than 10°C / min.
[0019] Furthermore, in step (4), the alloy plate subjected to the primary heat treatment is subsequently subjected to a secondary hot rolling deformation treatment, the alloy plate is directly placed in a 415-428°C heat treatment furnace for 10-40 minutes, and then subjected to hot rolling deformation, with a hot rolling deformation amount of 50-75%, a pass deformation amount of 10-20%, and unidirectional rolling.
[0020] Furthermore, in step (5), the hot-rolled plate is subsequently subjected to a secondary high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, with a heat treatment temperature of 460-500°C, a treatment time of 0-30h, a heating rate of 22-32°C / min, and a cooling rate greater than 10°C / min.
[0021] Furthermore, in step (6), a certain amount of primary cold rolling deformation (deformation 30-70%) + intermediate annealing treatment (380-440°C, 0.5h-4h) + secondary cold rolling treatment (deformation 30-70%) is sequentially performed, so that the alloy matrix precipitation phase and the iron-rich phase present a coupled gradient distribution feature.
[0022] Furthermore, in step (7), a high-temperature short-time solution treatment is performed, the solution temperature is 470-490°C, the heating rate is greater than 150°C / min, the quenching cooling rate after solution treatment is greater than 100°C / s, and the quenched sample is transferred to an aging furnace within 1 minute for a two-stage isothermal pre-aging treatment, the first stage temperature is 80-130°C / 1-10h, and the second stage temperature is 20-60°C / 15-90 days. The alloy sheet can exhibit excellent room temperature stamping forming performance.
[0023] Further, in step (8), the sample subjected to the double-stage pre-aging treatment is then subjected to non-isothermal heat treatment control, and the variable rate variable temperature aging process is set to three stages, namely, 100°C → 170°C (heating rate R H1 )→185℃(heating rate R H2 )→170℃(cooling rate R C1 )→100℃(cooling rate R C2 ), where R H1 =R C2 =10-20℃ / h, R H2 =R C1 =30-40℃ / h, raising the sample temperature to 185℃, or further cooling it to 170℃, the alloy can show high strength and high corrosion resistance.
[0024] The novel Al-Zn-Mg-Cu alloy sheet with high formability, high strength and high corrosion resistance developed by the present invention is very suitable for use in the production of automotive parts, especially for the manufacture of complex-shaped parts with high requirements on stamping forming performance, strength and corrosion resistance.
[0025] Beneficial effects of the present invention:
[0026] By adopting the above technical scheme, the present invention has the following advantages: the present invention can not only make the new Al-Zn-Mg-Cu alloy sheet form suitable fine-grain and coarse-grain coupled distribution organizational characteristics after the coordinated regulation of multiple processes of hot processing, but also can couple and regulate the distribution of its internal nano-precipitation phase and grain boundary precipitation phase; finally, based on the coupling effect of the above-mentioned organizational aspects, the developed new 7xxx series aluminum alloy sheet can show excellent room temperature stamping forming performance, and the aging state or simulated baking paint state (170-185℃ / 20-30min) can also have high strength and high corrosion resistance. The present invention can significantly improve the room temperature stamping forming performance of the alloy sheet, and the aging state or simulated baking paint state can also have high strength and high corrosion resistance, which has an important role in promoting the further wide application of the aluminum alloy sheet. The present invention is very suitable for the processing and production of aluminum alloy materials for automobile body structures, as well as for other aluminum alloy material production enterprises with specific requirements for the organizational characteristics and stamping forming performance of aluminum alloy sheets, and of course, it is also suitable for other technical industries with high requirements for the organization and comprehensive performance of other series of aluminum alloy materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A flow chart of a multi-process coordinated control method for aluminum alloy plates with high formability, high strength and high corrosion resistance;
[0028] Figure 2 TEM microstructure characterization results of the intermediate annealed state of the 2# alloy prepared in Example 1;
[0029] Figure 3 TEM microstructure characterization results of the intermediate annealed state of the 3# alloy prepared in Example 1;
[0030] Figure 4 SEM microstructure characterization results of the final cold-rolled state of the 1# alloy prepared in Example 1;
[0031] Figure 5 SEM microstructure characterization results of the final cold-rolled state of the 2# alloy prepared in Example 1;
[0032] Figure 6 SEM microstructure characterization results of the final cold-rolled state of the 3# alloy prepared in Example 1;
[0033] Figure 7EBSD characterization results of grain distribution morphology of No. 1 alloy plate prepared in Example 1 after single-stage pre-aging treatment;
[0034] Figure 8 EBSD characterization results of grain distribution morphology of No. 2 alloy plate prepared in Example 1 after single-stage pre-aging treatment;
[0035] Fig. 9 EBSD characterization results of grain distribution morphology of 3# alloy plate after single-stage pre-aging treatment in Example 1. DETAILED DESCRIPTION
[0036] The present invention is further supplemented and illustrated below in conjunction with specific implementation schemes.
[0037] Aiming at the research and application status that the room temperature stamping forming performance of high-strength Al-Zn-Mg-Cu alloy sheets for automobile body structural parts, the strength and corrosion resistance after simulated baking paint still need to be further improved, and the production cost urgently needs to be greatly reduced, the present invention proposes a method for coordinated regulation of multiple processes based on component design and hot processing, that is, by optimizing the Cu content and the solute element Fe content and matching ratio in the matrix, so that they react with each other to form a suitably distributed Al-FeCu phase, thereby suppressing the adverse effects of the Fe element and the reduction of corrosion resistance after excessive Cu element. The method can not only make the multi-scale dispersed particles of the developed alloy present a gradient distribution feature, but also make the fine grains and coarse grains present a coupled distribution feature. Finally, not only the single-stage pre-aging alloy sheet has high formability, but also the room temperature stamping forming performance can be further improved after double-stage pre-aging treatment; in addition, after the double-stage pre-aging alloy sheet is regulated by variable rate non-isothermal heat treatment, the simulated baking paint state can have both high strength and high corrosion resistance. The method of the present invention is very suitable for the manufacture of new aluminum alloys for automobiles, especially for the manufacture of parts with complex shapes that have high requirements for room temperature stamping performance, strength, corrosion resistance, etc.
[0038] According to the present invention, the high-formability Al-Zn-Mg-Cu alloy sheet for automobiles and the multi-process coordinated control method thereof, the raw materials are respectively recycled aluminum or ordinary aluminum, industrial pure Mg, industrial pure Zn, industrial pure Ni, intermediate alloys such as Al-20wt% Si, Al-50wt% Cu, Al-20wt% Fe, Al-10wt% Mn, Al-5wt% Cr, Al-10wt% Ti, etc. Figure 1 As shown, the following technical route is adopted:
[0039] Step 101: using recycled aluminum or ordinary aluminum to prepare an Al-Zn-Mg-Cu-Fe-Mn alloy with high formability, high strength and high corrosion resistance, then using medium frequency induction to melt the alloy under non-vacuum conditions, and casting it in a water-cooled steel mold, controlling the cooling rate to be greater than 40°C / min so that the alloy grain size, solute element segregation and primary phase distribution meet the subsequent regulation requirements;
[0040] Step 102: According to the as-cast structure, the ingot is subjected to a two-stage high-temperature heat treatment, wherein the first stage temperature is 390-430°C, the heating rate is 22-35°C / min, and the treatment time is 10-27h; the second stage temperature is 430-485°C, the heating rate is 22-35°C / min, and the treatment time is 10-27h; then the ingot subjected to the high-temperature heat treatment is further cooled to 410-438°C, the cooling rate is 5-15°C / min, and then hot rolling deformation treatment is performed on the ingot, and the hot rolling deformation amount is 40-68%;
[0041] Step 103: Then, the hot-rolled plate is subjected to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-510° C., and the treatment time is 0-30 hours;
[0042] Step 104: Subsequently, the alloy plate subjected to the primary heat treatment is subjected to secondary hot rolling deformation treatment, the alloy plate is directly placed in a 410-428° C. heat treatment furnace for 10-60 minutes, and then subjected to hot rolling deformation, with a hot rolling deformation amount of 50-80%;
[0043] Step 105: Then, the hot-rolled plate is subjected to secondary high-temperature heat treatment to adjust the distribution characteristics of alloy solute elements, with the heat treatment temperature being 460-510° C. and the treatment time being 0-30 h;
[0044] Step 106: then sequentially performing a certain amount of primary cold rolling deformation + intermediate annealing treatment + secondary cold rolling treatment, so that the alloy matrix precipitation phase and the iron-rich phase present a coupled gradient distribution feature;
[0045] Step 107: high temperature short time solution treatment, the solution temperature is 470-500°C, then the alloy sample after solution treatment is quenched and cooled from the solution treatment temperature to room temperature, and the quenched sample is transferred to an aging furnace within 1 minute for double-stage isothermal pre-aging treatment, the first stage temperature is 80-140°C, and the second stage temperature is 20-60°C;
[0046] Step 108: The sample subjected to the double-stage pre-aging treatment is then subjected to non-isothermal heat treatment control, and the variable-rate variable-temperature aging process is set to three stages, namely, 100°C → 170°C (heating rate R H1 )→185℃(heating rate R H2 )→170℃(cooling rate R C1 )→100℃(cooling rate RC2 ), where R H1 =R C2 =10-30℃ / h, R H2 =R C1 =30-50℃ / h, raise the sample temperature to 185℃, or further cool it to 170℃; the alloy can show high strength and high corrosion resistance.
[0047] Specifically, the treatment process comprises the following steps: firstly, all the recycled aluminum or ordinary aluminum is added into a crucible and melted, and the temperature is controlled at 780-880°C, then Al-20wt%Fe, Al-10wt%Mn, Al-10wt%Ti, Al-5wt%Cr, Al-20wt%Si master alloys are added respectively, and Al-50wt%Cu master alloy is added after melting, and then the melt is stirred at high power for 10 minutes, and then the required content of pure Ni is added into the melt and the melt is stirred at high power for 10 minutes, and then the temperature of the alloy melt is controlled to be above 720°C, and pure Zn and pure Mg are added respectively, when adding pure Mg, a graphite bell is used to press it into the bottom of the melt, and the bell is taken out after it is completely melted, and the power of the medium frequency induction furnace is adjusted to stabilize the temperature of the alloy melt at 740°C again, and then slag is removed and a refining agent is added to perform degassing and refining; then when the melt temperature drops to 720°C, Al-5wt%Ti is added. i-1wt% B grain refiner and properly stirred, and finally, after keeping the temperature at 720℃ for 10min, the melt was cast into a steel mold with water cooling on all sides, and the cooling rate was controlled to be greater than 40℃ / min. The specific chemical composition of the alloy of the invention is shown in Table 1:
[0048] Table 1 Chemical composition of alloys according to the present invention (mass percentage, wt%)
[0049] Zn Mg Cu Fe Mn Ni Cr Ti Si Al 1# 6 2.5 1.5 0.1-0.6 0.05-0.2 0.02-0.05 0.01-0.03 0.02-0.2 0.01-0.07 margin 2# 6 2.5 2.5 0.1-0.6 0.05-0.2 0.02-0.05 0.01-0.03 0.02-0.2 0.01-0.07 margin 3# 6 2.5 3.5 0.1-0.6 0.05-0.2 0.02-0.05 0.01-0.03 0.02-0.2 0.01-0.07 margin 4# 5 2.0 2.5 0.1-0.6 0.05-0.2 0.02-0.05 0.01-0.03 0.02-0.2 0.01-0.07 margin 5# 7 1.5 2.5 0.1-0.6 0.05-0.2 0.02-0.05 0.01-0.03 0.02-0.2 0.01-0.07 margin
[0050] In order to construct the expected multi-scale iron-rich phase and precipitate phase coupled distribution structure characteristics, the ingot was subjected to the following multi-process coordinated control treatment: (1) the ingot was subjected to a two-stage high-temperature heat treatment, with the first stage temperature of 390-415°C, a heating rate of 22-32°C / min, and a treatment time of 10-27h; the second stage temperature of 430-485°C, a heating rate of 22-32°C / min, and a treatment time of 10-27h; then the ingot subjected to high-temperature heat treatment was further cooled to 410-428°C, with a cooling rate of 10-15°C / min, and then hot rolled. 40-68%, deformation per pass 10-20%, unidirectional rolling; (2) subjecting the hot-rolled plate to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-500°C, the treatment time is 0-30h, the heating rate is 22-32°C / min, and the cooling rate is greater than 10°C / min; (3) subjecting the alloy plate regulated by the first heat treatment to a secondary hot rolling deformation treatment, directly placing the alloy plate in a 415-428°C heat treatment furnace for 10-40min, and then subjecting it to hot rolling deformation, the hot rolling deformation is 50-75%, the deformation per pass is 10 -20%, unidirectional rolling; (4) then subjecting the hot-rolled plate to secondary high-temperature heat treatment to control the distribution characteristics of the alloy solute elements, with a heat treatment temperature of 460-500°C, a treatment time of 0-30h, a heating rate of 22-32°C / min, and a cooling rate greater than 10°C / min; (5) then subjecting the hot-rolled plate to a certain amount of primary cold rolling deformation (deformation 30-70%) + intermediate annealing treatment (380-440°C, 0.5h-4h) + secondary cold rolling treatment (deformation 30-70%), so that the alloy matrix precipitation phase and the iron-rich phase present a coupled gradient distribution characteristic; (6) high temperature short-time solidification Solution treatment, solution temperature 470-490℃, heating rate greater than 150℃ / min, quenching cooling rate greater than 100℃ / s after solution treatment, transfer the quenched sample to the aging furnace within 1min for double-stage isothermal pre-aging treatment, the first stage temperature is 80-130℃ / 1-10h, the second stage temperature is 20-60℃ / 15-90 days, the alloy plate can show excellent room temperature stamping forming performance; (7) then the double-stage pre-aging treated sample is subjected to non-isothermal heat treatment regulation, and the variable rate variable temperature aging process is set to three stages, namely, 100℃→170℃ (heating rate R H1 )→185℃(heating rate R H2 )→170℃(cooling rate R C1 )→100℃(cooling rate R C2 ), where R H1 =R C2 =10-20℃ / h, R H2 =R C1=30-40℃ / h, the sample is heated to 185℃ or further cooled to 170℃, the alloy plate can show high strength and high corrosion resistance. The specific implementation is as follows: Example 1
[0051] Implementation of the invention Alloys 1#, 2# and 3# are melted and cast by medium frequency induction as follows. The alloy melting process using medium frequency induction under non-vacuum conditions is as follows: first, all the recycled aluminum or ordinary aluminum is added to a crucible and melted, and the temperature is controlled at 780-880°C. Then, Al-20wt%Fe, Al-10wt%Mn, Al-10wt%Ti, Al-5wt%Cr, and Al-20wt%Si master alloys are added respectively. After melting, Al-50wt%Cu master alloy is added. Then, the melt is stirred at high power for 10 minutes, and then the required content of pure N is added. i into the melt and stir the melt at high power for 10 minutes, then control the temperature of the alloy melt to above 720°C, add pure Zn and pure Mg respectively, use a graphite bell to press it into the bottom of the melt when adding pure Mg, remove the bell after it is completely dissolved, adjust the power of the medium frequency induction furnace to stabilize the temperature of the alloy melt at 740°C, then remove the slag, add a refining agent for degassing and refining; then add Al-5wt% T when the melt temperature drops to 720°C i-1wt% B grain refiner and stir appropriately, finally keep the temperature at 720℃ for 10min and then cast the melt into a water-cooled steel mold on all sides, and control the cooling rate to be greater than 40℃ / min; perform two-stage high-temperature heat treatment on the ingot, the first stage temperature is 390-415℃, the heating rate is 22-32℃ / min, the treatment time is 10-27h, the second stage temperature is 430-485℃, the heating rate is 22-32℃ / min, and the treatment time is 10-27h; then the ingot treated with high temperature heat is further cooled to 410-428℃, the cooling rate is 10-15℃ / min, and then hot rolling deformation treatment is performed on it, the hot rolling deformation is 40-68%, the pass deformation is 10-20%, and unidirectional rolling; the hot-rolled plate is subjected to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, and the heat treatment The temperature is 460-500℃, the treatment time is 0-30h, the heating rate is 22-32℃ / min, and the cooling rate is greater than 10℃ / min; then the alloy plate regulated by the primary heat treatment is subjected to secondary hot rolling deformation treatment, the alloy plate is directly placed in a 415-428℃ heat treatment furnace for 10-40min, and then hot rolled, the hot rolling deformation is 50-75%, the pass deformation is 10-20%, and unidirectional rolling; then the hot rolled plate is subjected to secondary high-temperature heat treatment to regulate the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-500℃, the treatment time is 0-30h, the heating rate is 22-32℃ / min, and the cooling rate is greater than 10℃ / min; then a certain amount of primary cold rolling deformation (deformation 30-70%) + intermediate annealing treatment (380-440℃, 0.5h-4h) + secondary cold rolling treatment (deformation 30-70%), so that the alloy matrix precipitation phase and the iron-rich phase are coupled with gradient distribution characteristics; then high temperature short-time solution treatment, the solution temperature is 470-490℃, the heating rate is greater than 150℃ / min, the quenching cooling rate after solution is greater than 100℃ / s, the quenched sample is transferred to the aging furnace within 1min for single-stage isothermal pre-aging treatment, the temperature is 80-130℃ / 1-10h; finally, the mechanical properties of 1#, 2# and 3# alloy plates treated with single-stage isothermal pre-aging are measured, and the corresponding mechanical properties are shown in Table 2. The TEM organization of the corresponding intermediate annealing state dispersed particles in the hot working process of 2# and 3# alloys is shown in Table 2. Figure 2 ,3, the corresponding final cold-rolled SEM structure is as follows Figure 4 ,5 and 6, the EBSD microstructures of 1#, 2# and 3# alloys after single-stage pre-aging control are as follows Figure 7 , 8 and 9.
[0052] Example 2
[0053] Implementation of the invention Alloys 1#, 2# and 3# are melted and cast by medium frequency induction as follows. The alloy melting process using medium frequency induction under non-vacuum conditions is as follows: first, all the recycled aluminum or ordinary aluminum is added to a crucible and melted, and the temperature is controlled at 780-880°C. Then, Al-20wt%Fe, Al-10wt%Mn, Al-10wt%Ti, Al-5wt%Cr, and Al-20wt%Si master alloys are added respectively. After melting, Al-50wt%Cu master alloy is added. Then, the melt is stirred at high power for 10 minutes, and then the required content of pure N is added. i into the melt and stir the melt at high power for 10 minutes, then control the temperature of the alloy melt to above 720°C, add pure Zn and pure Mg respectively, use a graphite bell to press it into the bottom of the melt when adding pure Mg, remove the bell after it is completely dissolved, adjust the power of the medium frequency induction furnace to stabilize the temperature of the alloy melt at 740°C, then remove the slag, add a refining agent for degassing and refining; then add Al-5wt% T when the melt temperature drops to 720°C i-1wt% B grain refiner and stir appropriately, finally keep the temperature at 720℃ for 10min and then cast the melt into a water-cooled steel mold on all sides, and control the cooling rate to be greater than 40℃ / min; perform two-stage high-temperature heat treatment on the ingot, the first stage temperature is 390-415℃, the heating rate is 22-32℃ / min, the treatment time is 10-27h, the second stage temperature is 430-485℃, the heating rate is 22-32℃ / min, and the treatment time is 10-27h; then the ingot treated with high temperature heat is further cooled to 410-428℃, the cooling rate is 10-15℃ / min, and then hot rolling deformation treatment is performed on it, the hot rolling deformation is 40-68%, the pass deformation is 10-20%, and unidirectional rolling; the hot-rolled plate is subjected to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, and the heat treatment The temperature is 460-500℃, the treatment time is 0-30h, the heating rate is 22-32℃ / min, and the cooling rate is greater than 10℃ / min; then the alloy plate regulated by the primary heat treatment is subjected to secondary hot rolling deformation treatment, the alloy plate is directly placed in a 415-428℃ heat treatment furnace for 10-40min, and then hot rolled, the hot rolling deformation is 50-75%, the pass deformation is 10-20%, and unidirectional rolling; then the hot rolled plate is subjected to secondary high-temperature heat treatment to regulate the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-500℃, the treatment time is 0-30h, the heating rate is 22-32℃ / min, and the cooling rate is greater than 10℃ / min; then a certain amount of primary cold rolling deformation (deformation 30-70%) + intermediate annealing treatment (380-440℃, 0.5h-4h) + secondary cold rolling treatment (deformation 30-70%), so that the alloy matrix precipitation phase and the iron-rich phase have a coupled gradient distribution characteristic; then high-temperature short-time solid solution treatment, the solid solution temperature is 470-490℃, the heating rate is greater than 150℃ / min, the quenching cooling rate after solid solution is greater than 100℃ / s, and the quenched sample is transferred to the aging furnace within 1min for double-stage isothermal pre-aging treatment, the first stage temperature is 80-130℃ / 1-10h, and the second stage temperature is 20-60℃ / 15-90 days; finally, the mechanical properties of 1#, 2# and 3# alloy plates treated with double-stage isothermal pre-aging are measured, and the corresponding mechanical properties are shown in Table 2. .
[0054] Example 3
[0055] Implementation of the invention Alloys 1#, 2# and 3# are melted and cast by medium frequency induction as follows. The alloy melting process using medium frequency induction under non-vacuum conditions is as follows: first, all the recycled aluminum or ordinary aluminum is added to a crucible and melted, and the temperature is controlled at 780-880°C. Then, Al-20wt%Fe, Al-10wt%Mn, Al-10wt%Ti, Al-5wt%Cr, and Al-20wt%Si master alloys are added respectively. After melting, Al-50wt%Cu master alloy is added. Then, the melt is stirred at high power for 10 minutes, and then the required content of pure N is added. i into the melt and stir the melt at high power for 10 minutes, then control the temperature of the alloy melt to above 720°C, add pure Zn and pure Mg respectively, use a graphite bell to press it into the bottom of the melt when adding pure Mg, remove the bell after it is completely dissolved, adjust the power of the medium frequency induction furnace to stabilize the temperature of the alloy melt at 740°C, then remove the slag, add a refining agent for degassing and refining; then add Al-5wt% T when the melt temperature drops to 720°C i-1wt% B grain refiner and stir appropriately, finally keep the temperature at 720℃ for 10min and then cast the melt into a water-cooled steel mold on all sides, and control the cooling rate to be greater than 40℃ / min; perform two-stage high-temperature heat treatment on the ingot, the first stage temperature is 390-415℃, the heating rate is 22-32℃ / min, the treatment time is 10-27h, the second stage temperature is 430-485℃, the heating rate is 22-32℃ / min, and the treatment time is 10-27h; then the ingot treated with high temperature heat is further cooled to 410-428℃, the cooling rate is 10-15℃ / min, and then hot rolling deformation treatment is performed on it, the hot rolling deformation is 40-68%, the pass deformation is 10-20%, and unidirectional rolling; the hot-rolled plate is subjected to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, and the heat treatment The temperature is 460-500℃, the treatment time is 0-30h, the heating rate is 22-32℃ / min, and the cooling rate is greater than 10℃ / min; then the alloy plate regulated by the primary heat treatment is subjected to secondary hot rolling deformation treatment, the alloy plate is directly placed in a 415-428℃ heat treatment furnace for 10-40min, and then hot rolled, the hot rolling deformation is 50-75%, the pass deformation is 10-20%, and unidirectional rolling; then the hot rolled plate is subjected to secondary high-temperature heat treatment to regulate the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-500℃, the treatment time is 0-30h, the heating rate is 22-32℃ / min, and the cooling rate is greater than 10℃ / min; then a certain amount of primary cold rolling deformation (deformation 30-70%) + intermediate annealing treatment (380-440℃, 0.5h-4h) + secondary cold rolling treatment (deformation 30-70%), so that the alloy matrix precipitation phase and the iron-rich phase present a coupled gradient distribution feature; then high-temperature short-time solution treatment is carried out, the solution temperature is 470-490℃, the heating rate is greater than 150℃ / min, the quenching cooling rate after solution is greater than 100℃ / s, and the quenched sample is transferred to the aging furnace within 1min for double-stage isothermal pre-aging treatment, the first stage temperature is 80-130℃ / 1-10h, and the second stage temperature is 20-60℃ / 15-90 days; then the rolling direction sample treated with double-stage pre-aging is subjected to non-isothermal heat treatment regulation, and the variable rate variable temperature aging process is set to three stages, namely, 100℃→170℃ (heating rate R. H1 )→185℃(heating rate R H2 )→170℃(cooling rate R C1 )→100℃(cooling rate R C2 ), where R H1 =R C2 =10-20℃ / h, R H2 =R C1 =30-40℃ / h, the sample treatment rate was raised to 185℃, and then further cooled to 170℃; finally, the mechanical properties and intergranular corrosion resistance of 1#, 2# and 3# alloy plates treated with variable rate non-isothermal aging were measured (according to ASTM G110 standard), and the corresponding mechanical properties and intergranular corrosion depths are shown in Table 3
[0056] Table 2 Summary of tensile properties of pre-aged alloy plates after different heat treatment processes
[0057]
[0058]
[0059] Table 3 Summary of tensile and corrosion properties of alloy plates after variable rate non-isothermal heat treatment
[0060] alloy δ / % <![CDATA[σ 0.2 / MPa]]> <![CDATA[σ b / MPa]]> Corrosion depth / μm Alloy 1# corresponding to Example 3 11 532 566 90 Alloy 2# corresponding to Example 3 12 545 580 96 Alloy 3# corresponding to Example 3 11 537 570 95
[0061] In recent years, with the acceleration of the lightweight process of automobiles, the amount of aluminum used in the outer and inner panels of the car body has gradually increased. However, if the body structure still uses steel structural parts, it will inevitably cause problems such as difficulty in connecting steel and aluminum and corrosion of heterogeneous metals, which is extremely unfavorable for the rapid development of aluminum alloys for lightweight automobiles. Therefore, it is urgent to develop high-strength 7xxx series aluminum alloy sheets and preparation methods for body structural parts. However, the room temperature forming performance of this series of aluminum alloys needs to be further improved, and how to ensure high strength and high corrosion resistance in the simulated baking process (170-185℃ / 20-30min) after stamping is a key issue affecting its wide application. In order to further reduce the production cost of this series of alloy sheets, it is necessary to make full use of recycled aluminum to melt and cast this series of alloys. However, recycled aluminum generally contains the impurity element Fe, which is very easy to produce dendritic, rod-shaped or coarse granular iron-rich phases in the cast alloy. Although these phases can be broken during the subsequent hot working process, it is inevitable that there will be coarse iron-rich phase particles that are not completely broken in the final alloy matrix, and there will be residual microcracks and uneven distribution inside, which will affect the plasticity, forming performance and corrosion resistance of the alloy. Therefore, it is necessary to optimize the composition design and coordinate the subsequent hot working multi-process to effectively control its size, morphology and distribution, so that the stamping forming performance of the alloy sheet can be significantly improved, and the strength will not be reduced in the subsequent simulated baking process. The present invention makes full use of the solute element Fe that is generally contained in the high content of recycled aluminum or ordinary aluminum. By increasing the Cu content, it can not only be dissolved in the alloy matrix, but also form a concentration gradient distribution feature with the Fe element in the cast state, and further form a multi-scale gradient distribution Al FeCu phase through subsequent hot rolling and high temperature heat treatment; at the same time, with the change of hot working process, the size matching, morphology and distribution of these phases can change significantly, which has an important impact on the alloy organization and texture evolution. In particular, the multi-scale iron-rich phase with gradient distribution characteristics in the alloy matrix during the subsequent high-temperature solution heat treatment will have a positive effect on the alloy recrystallization nucleation, that is, coarse particles can induce recrystallization nucleation, while fine particles can effectively hinder the rapid growth of recrystallization, which will eventually effectively refine the grains and significantly weaken the texture, and the stamping performance of the pre-aged alloy sheet can be significantly improved. In addition, due to the increase in the solute element Cu content, a large number of solute atomic clusters can be further precipitated on the original basis through double-stage pre-aging regulation, which can improve the coordinated deformation ability between grains in the alloy matrix and further improve the stamping performance of the alloy sheet.For pre-aged alloy plates, if they are subjected to variable-rate non-isothermal heat treatment, not only can the precipitation of continuous precipitate phases at grain boundaries be effectively inhibited, thereby greatly improving the corrosion resistance of the alloy, but a large number of multi-scale precipitate phases can also be precipitated in the alloy matrix, so that the alloy plates can still exhibit high-strength characteristics after simulated baking paint (170-185℃ / 20-30min), while the strength will be reduced after the traditional isothermal aging process is regulated and then subjected to simulated baking paint treatment.
[0062] According to the TEM microstructures of the intermediate annealed alloys 1#, 2# and 3# prepared in Example 1, it can be seen that with the increase of Cu content, the number of dispersed particles in the alloy matrix increases significantly. In addition to the iron-rich phase, these particles also have a large number of precipitate phases. Moreover, with the increase of Cu content, the multi-scale dispersion distribution characteristics become more obvious (such as Figure 2-4 In addition, further SEM microstructure observation of the final cold-rolled state shows more clearly that the increase in Cu content is very conducive to the formation of multi-scale dispersed particles, that is, the size of coarse particles increases, while the number density of fine particles increases significantly (as shown in Figure 2). Figure 4 and 7 As shown). The formation of these dispersed particles will have a significant impact on the recrystallization process of the alloy solution, that is, the coarse particles will stimulate nucleation, inducing more recrystallized grains, while the fine dispersed particles in the matrix will hinder the rapid growth of recrystallized grains. The final alloy not only has relatively small grains, but also has a significantly weakened texture. The plastic strain ratio r value of the single-stage pre-aging state of the series of alloy plates characterizing the stamping forming performance is relatively high, but compared with other alloys, the average plastic strain ratio of the 3# alloy is better, up to 0.691, and the anisotropy index Δr value is only -0.004. In addition to achieving the above effects through component design and process control, it is precisely because of the reasonable design and matching of the Cu content and the Fe content, coupled with the control of the cold rolling deformation and deformation passes during the hot working process, that the 3# alloy in Example 1 also has a clear gradient structure, that is, the surface grains are fine and the core grains are coarse. This gradient structure is more conducive to the improvement of the alloy stamping forming performance and the reduction of anisotropy. This is mainly because after the Cu content increases, the number density of multi-scale dispersed particles in the alloy matrix increases, and a large number of dislocations and strain energy storage can be generated on the surface by applying a small deformation, while the core has fewer dislocations and lower strain energy storage. In the subsequent solid solution process, the alloy can be recrystallized first on the surface, and the strong pinning and hindrance of the fine dispersed particles make it difficult for the formed recrystallized grains to grow; while the core has a lower nucleation rate, and the recrystallized grains are relatively coarse. This ultimately leads to the above-mentioned gradient organizational characteristics in the alloy matrix, which significantly improves the stamping performance of the alloy.
[0063] The room temperature stamping forming performance of the above-mentioned invention alloy is relatively excellent after the single-stage pre-aging regulation described in Example 1, but the stamping forming performance of the traditional pre-aged alloy is generally reduced as the solute atom clusters are precipitated during the natural placement process. However, in comparison, after the first-stage pre-aging regulation of the alloy of the present invention, even after 20-60℃ / 15-90 days of treatment (the technical route shown in Example 2), the alloy 2# and 3# plates will precipitate solute atom clusters due to the increase in the solute element Cu content, but the precipitated solute atom clusters further promote the coordinated deformation of the alloy plate. Finally, after the double-stage pre-aging regulation, the average plastic strain ratio characterizing the stamping forming performance of the alloy plate has increased, especially the 3# alloy has the largest increase (as shown in Table 2). This is very beneficial for the actual production and application of the alloy plate of this series, and effectively avoids the problems of increased strength and reduced stamping forming performance caused by the natural placement of the alloy plate during the subsequent transportation process after the first-stage pre-aging regulation.
[0064] The series of invention alloys can show excellent room temperature stamping forming performance after being regulated by Examples 1 and 2, but as a body structural part, it also needs to have high strength characteristics. Therefore, it is necessary to further regulate its aging in order to greatly improve the strength of the alloy sheet. Traditional processes generally use isothermal aging, such as isothermal aging at 120°C for 20-24h. Although it can obtain high strength, the prepared automotive parts are prone to Mg-Zn precipitation phase (such as η′ phase) dissolving back during subsequent high-temperature baking paint (170-185°C / 20-30min), resulting in a significant reduction in strength and other problems. To this end, the present invention optimizes and increases the Cu content and other components to form more multi-scale dispersed particles to affect the recrystallization structure, and also intends to regulate the non-isothermal variable rate heat treatment to enable more relatively stable nano Al ZnMgCu precipitation phases, such as S phase or T phase, to be precipitated in the alloy matrix, so that the alloy will not only not decrease in strength but also increase during the baking paint process. As shown in Example 3, after the alloy plate after double-stage pre-aging regulation is further regulated by variable rate non-isothermal heat treatment, when the temperature is lowered to 170°C (which includes 170-185°C / 20-30min simulated paint baking process), the alloy strength has increased significantly, and the yield strength of 1#, 2# and 3# alloys are all above 530MPa (as shown in Table 3). Moreover, since the heat treatment process is non-isothermal heat treatment regulation, discontinuous precipitation phases will precipitate at the grain boundaries. The intergranular corrosion performance evaluation of the alloy after simulated paint baking is carried out in accordance with the ASTM-G110 standard. The corrosion depth corresponding to the sample after corrosion is observed and measured by SEM. The measurement results show that the developed series of alloy plates are also excellent in corrosion resistance under high strength state (as shown in Table 3). The above performances are significantly higher than the corresponding performances of the current international mainstream 7xxx series aluminum alloy plates.
[0065] In summary, the present invention not only significantly improves the size, morphology and distribution of the original iron-rich phase in the alloy matrix by coordinating the multi-process of hot processing on the new Al-Zn-Mg-Cu-Fe alloy ingot, but also makes full use of the positive influence of the multi-scale dispersed particles composed of the coarse Al-FeCu phase and the precipitate phase formed by the reaction of high-concentration Cu and Fe on the alloy recrystallization process, so that the alloy sheet presents a fine-grained structure or a gradient structure with fine grains on the surface and coarse grains in the core, thereby significantly increasing the coordinated deformation ability of the alloy sheet and significantly improving its room temperature stamping forming performance; and due to the reasonable composition design and process control, the alloy sheet after the first-stage pre-aging treatment will not only not reduce its stamping forming performance after being naturally placed for a long time, but also significantly increase it. This is very beneficial for the production of automotive structural parts. In addition, according to the characteristics of the developed alloy, after the precipitation of the multi-scale precipitate phase is regulated by non-isothermal variable rate heat treatment, the alloy can not only effectively avoid the phenomenon of strength reduction after the simulated baking paint treatment after isothermal aging of the traditional alloy, but also achieve the strength increase after the simulated baking paint. At the same time, it also has excellent resistance to intergranular corrosion under high-strength conditions. All these excellent comprehensive properties indicate that the new aluminum alloy material and its preparation method are very suitable for the manufacture of automotive body structural parts, and also play an important role in promoting the rapid development of aluminum alloys for lightweight automobiles. In addition, it also has certain guiding significance for the development, processing and application of high-formability, high-strength and high-corrosion-resistant aluminum alloys in other fields. It is worthy for automobile manufacturers and aluminum alloy processing companies to pay attention to this invention so that it can be promoted and applied in this field as soon as possible.
[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an aluminum alloy sheet having high formability, high strength and high corrosion resistance, characterized in that: The aluminum alloy is an Al-Zn-Mg-Cu-Fe-Mn alloy, and its chemical composition and mass percentage are as follows: Zn: 5.0-7.0wt%, Mg: 1.0-3.0wt%, Cu: 1.5-4.0wt%, Fe: 0.1-0.6wt%, Mn: 0.05-0.2wt%, Ni: 0.02-0.05wt%, Ti: 0.02-0.2wt%, Cr: 0.01-0.03wt%, Si: 0.01-0.07wt%, and the balance is Al; The specific preparation steps are as follows: (1) Using recycled aluminum or ordinary aluminum to prepare Al-Zn-Mg-Cu-Fe-Mn alloys with high formability, high strength and high corrosion resistance, then using medium frequency induction melting under non-vacuum conditions, and casting them in a water-cooled steel mold, the cooling rate is controlled to be greater than 40°C / min so that the alloy grain size, solute element segregation and primary phase distribution meet the subsequent regulation requirements; (2) According to the as-cast structure, the ingot is subjected to a two-stage high-temperature heat treatment, wherein the first stage temperature is 390-430°C, the heating rate is 22-35°C / min, and the treatment time is 10-27h; the second stage temperature is 430-485°C, the heating rate is 22-35°C / min, and the treatment time is 10-27h; then the ingot subjected to the high-temperature heat treatment is further cooled to 410-438°C, the cooling rate is 5-15°C / min, and then hot rolling deformation treatment is performed on it, and the hot rolling deformation amount is 40-68%; (3) Then, the hot-rolled plate is subjected to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-510° C., and the treatment time is 0-30 h; (4) Subsequently, the alloy plate subjected to the primary heat treatment is subjected to a secondary hot rolling deformation treatment, the alloy plate is directly placed in a 410-428° C. heat treatment furnace for 10-60 min, and then subjected to hot rolling deformation, with a hot rolling deformation amount of 50-80%; (5) The hot-rolled plate is then subjected to secondary high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, with the heat treatment temperature being 460-510° C. and the treatment time being 0-30 h; (6) then sequentially performing a certain amount of primary cold rolling deformation + intermediate annealing treatment + secondary cold rolling treatment, so that the alloy matrix precipitation phase and the iron-rich phase present a coupled gradient distribution characteristic; (7) High temperature short time solution treatment, solution temperature 470-500℃, then quenching and cooling the alloy sample from the solution treatment temperature to room temperature, transferring the quenched sample to the aging furnace within 1 min for double-stage isothermal pre-aging treatment, the first stage temperature is 80-140℃, the second stage temperature is 20-60℃, the alloy sheet can show excellent room temperature stamping performance at room temperature; (8) The samples treated with double-stage pre-aging were then subjected to non-isothermal heat treatment, and the variable-rate variable-temperature aging process was set to three stages, namely, 100°C → 170°C (heating rate R H1 )→185℃(heating rate R H2 )→170℃(cooling rate R C1 )→100℃(cooling rate R C2 ), where R H1 =R C2 =10-30℃ / h, R H2 =R C1 =30-50℃ / h, raise the sample temperature to 185℃, or further cool it to 170℃; the alloy can show high strength and high corrosion resistance.
2. A method for preparing an aluminum alloy plate having high formability, high strength and high corrosion resistance according to claim 1, wherein in step (1) of the preparation method, the alloy is smelted by medium frequency induction under non-vacuum conditions: first, all the recycled aluminum or ordinary aluminum is added to a crucible and melted, and the temperature is controlled at 780-880°C, and then Al-20wt% Fe, Al-10wt% Mn, Al-10wt% Ti, Al-5wt% Cr, Al-20wt% Si master alloys are added respectively, and Al-50wt% Cu master alloy is added after melting, and then the melt is stirred at high power for 9-11 minutes, and then the required content of pure Ni is added into the melt and the melt is stirred at high power for 9-11 minutes, then the temperature of the alloy melt is controlled to be above 720°C, pure Zn and pure Mg are added respectively, when adding pure Mg, it is pressed into the bottom of the melt by a graphite bell jar, and the bell jar is taken out after it is completely dissolved, and the power of the medium frequency induction furnace is adjusted to stabilize the temperature of the alloy melt at 740°C again, then the slag is removed, and a refining agent is added for degassing and refining; then when the melt temperature is reduced to 720°C, an Al-5wt%Ti-1wt%B grain refiner is added and properly stirred, and finally, after keeping the temperature at 720°C for 10 minutes, the melt is cast into a steel mold with water cooling on all sides, and the cooling rate is controlled to be greater than 40°C / min.
3. According to the method for preparing an aluminum alloy plate with high formability, high strength and high corrosion resistance as described in claim 1, in step (2) of the preparation method, the ingot is subjected to a two-stage high-temperature heat treatment, the first stage temperature is 390-415°C, the heating rate is 22-32°C / min, the treatment time is 10-27h, the second stage temperature is 430-485°C, the heating rate is 22-32°C / min, and the treatment time is 10-27h; then the ingot subjected to the high-temperature heat treatment is further cooled to 410-428°C, the cooling rate is 10-15°C / min, and then it is subjected to hot rolling deformation treatment, the hot rolling deformation amount is 40-68%, the pass deformation amount is 10-20%, and unidirectional rolling.
4. According to the method for preparing an aluminum alloy plate with high formability, high strength and high corrosion resistance as described in claim 1, in step (3) of the preparation method, the hot-rolled plate is subjected to a high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-500°C, the treatment time is 0-30h, the heating rate is 22-32°C / min, and the cooling rate is greater than 10°C / min.
5. According to the method for preparing an aluminum alloy plate with high formability, high strength and high corrosion resistance as described in claim 1, in step (4) of the preparation method, the alloy plate that has been regulated by the primary heat treatment is subsequently subjected to a secondary hot rolling deformation treatment, and the alloy plate is directly placed in a 415-428°C heat treatment furnace for insulation for 10-40 minutes, and then hot rolled, with a hot rolling deformation amount of 50-75%, a pass deformation amount of 10-20%, and unidirectional rolling.
6. According to the method for preparing an aluminum alloy plate with high formability, high strength and high corrosion resistance as described in claim 1, in step (5) of the preparation method, the hot-rolled plate is subsequently subjected to a secondary high-temperature heat treatment to adjust the distribution characteristics of the alloy solute elements, the heat treatment temperature is 460-500°C, the treatment time is 0-30h, the heating rate is 22-32°C / min, and the cooling rate is greater than 10°C / min.
7. According to the method for preparing an aluminum alloy plate with high formability, high strength and high corrosion resistance as described in claim 1, in step (6) of the preparation method, a certain amount of primary cold rolling deformation, deformation amount 30-70% + intermediate annealing treatment: 380-440℃, 0.5h-4h + secondary cold rolling treatment: deformation amount 30-70% are subsequently carried out in sequence, so that the alloy matrix precipitation phase and the iron-rich phase have a coupled gradient distribution feature.
8. According to the method for preparing an aluminum alloy plate with high formability, high strength and high corrosion resistance as described in claim 1, in step (7) of the preparation method, high temperature short-time solution treatment is performed, the solution temperature is 470-490°C, the heating rate is greater than 150°C / min, the quenching cooling rate after solution treatment is greater than 100°C / s, the quenched sample is transferred to an aging furnace within 1 minute for two-stage isothermal pre-aging treatment, the first stage temperature is 80-130°C / 1-10h, and the second stage temperature is 20-60°C / 15-90 days, the alloy plate can exhibit excellent room temperature stamping forming performance.
9. According to the method for preparing an aluminum alloy sheet with high formability, high strength and high corrosion resistance as described in claim 1, in step (8) of the preparation method, the sample subjected to the double-stage pre-aging treatment is subsequently subjected to non-isothermal heat treatment control, and the variable rate variable temperature aging process is set to three stages, namely, 100°C → 170°C (heating rate R H1 )→185℃(heating rate R H2 )→170℃(cooling rate R C1 )→100℃(cooling rate R C2 ), where R H1 =R C2 =10-20℃ / h, R H2 =R C1 =30-40℃ / h, raise the sample temperature to 185℃, or further cool it to 170℃; the alloy can show high strength and high corrosion resistance.